2020
DOI: 10.3847/2041-8213/ab77c8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Late-stage Nuclear Burning on Red Supergiant Supernova Light Curves

Abstract: Many Type II supernovae (SNe) show hot early (∼30 days) emission, and a diversity in their light curves extending from the Type IIP to the Type IIL, which can be explained by interaction with dense and confined circumstellar material (CSM). We perform hydrodynamical simulations of red supergiants to model the ejection of CSM caused by wave heating during late-stage nuclear burning. Even a small amount of deposited energy (10 46 − 10 47 erg), which is roughly that expected due to waves excited by convection in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 33 publications
4
58
0
1
Order By: Relevance
“…Recent studies of observational data have shown that pre-SN activity may be important for explaining the shape of the light curve (Moriya et al 2017(Moriya et al , 2018Morozova et al 2017Morozova et al , 2018, though too much wave heat (or heat deposited over too long a duration) is inconsistent with typical Type II-P SNe (Ouchi & Maeda 2019). Instead, more impulsive wave heating is favored based on light-curve modeling of SN 2017eaw, confirming that such energy deposition can better reproduce SN light curves (Morozova et al 2020).…”
Section: Pre-supernova Stellar Evolutionmentioning
confidence: 89%
“…Recent studies of observational data have shown that pre-SN activity may be important for explaining the shape of the light curve (Moriya et al 2017(Moriya et al , 2018Morozova et al 2017Morozova et al , 2018, though too much wave heat (or heat deposited over too long a duration) is inconsistent with typical Type II-P SNe (Ouchi & Maeda 2019). Instead, more impulsive wave heating is favored based on light-curve modeling of SN 2017eaw, confirming that such energy deposition can better reproduce SN light curves (Morozova et al 2020).…”
Section: Pre-supernova Stellar Evolutionmentioning
confidence: 89%
“…If we adopt the progenitor radius of 827 R as the inner CSM radius, the total CSM mass of our best fit model is found to be 0.07 M by integrating Equation 6 over r. If we interpret this wind as that of a typical RSG, adopting a wind speed of 10 km s −1 , the mass-loss rate would be 0.06 M yr −1 within a timescale of 14 months, much higher than the steady winds observed in RSGs (Smith 2014). The possible explanation is that such dense CSM may originate from pre-SN outbursts due to the late-stage nuclear burning in the stellar interior (Quataert & Shiode 2012;Smith & Arnett 2014;Fuller 2017;Ouchi & Maeda 2019;Morozova et al 2020). Due to the presence of dense CSM around the SN, it is also expected to see flash signatures in the early spectrum (Yaron et al 2017;Nakaoka et al 2018;Rui et al 2019).…”
Section: From Hydrodynamic Modellingmentioning
confidence: 97%
“…In a hydrogen-rich envelope, the larger binding energy may prevent total envelope disruption, but the envelope's density profile may be altered and a small amount of marginally bound CSM may also be produced (Fuller 2017). This type of very confined CSM potentially contributes to early peaks in some Type II-P SN light curves (Moriya et al 2011;Morozova et al 2017;Das & Ray 2017;Moriya et al 2018;Morozova et al 2020). The CSM structure depends on the details of the heating history, as slow and steady heating will inflate the star without producing CSM and will not match observations of Type II-P SNe (Ouchi & Maeda 2019).…”
Section: Implications For Supernovae and Their Progenitorsmentioning
confidence: 99%
“…However, our models typically exhibit sharp spikes in the wave-heating rate at the onset of nuclear burning phases. This sudden wave heating can likely launch shocks that propagate through the stellar envelope, potentially unbinding material at the surface rather than inflating the entire star (Morozova et al 2020;Leung & Fuller 2020). More detailed hydrodynamic modeling should be performed to determine the pre-SN stellar/CSM density profile resulting from these outbursts.…”
Section: Implications For Supernovae and Their Progenitorsmentioning
confidence: 99%